ANALISIS RESPONS GURU TERHADAP PERILAKU REPETITIF ANAK DENGAN SPEKTRUM AUTISME DI SKHN 01 KOTA SERANG - Tia Fairuz Nabilah; Yahdinil Firda Nadirah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze and understand the forms of repetitive behaviors exhibited by a child with autism spectrum disorder at Sekolah Khusus Negeri (SKhN) 01 Kota Serang, as well as to explore the teacher’s strategies in managing these behaviors during classroom activities. The research employed a descriptive qualitative method, with data collected through direct observation and semi-structured interviews with the supporting teacher and a nine-year-old autistic student named Davin. The results indicate that D frequently displayed repetitive behaviors such as body rocking, hand rubbing, and meaningless humming, especially during tasks requiring concentration or while waiting for his turn. The teacher applied the Applied Behavior Analysis (ABA) approach using redirection and positive reinforcement strategies to reduce the frequency of such behaviors. An empathetic approach and structured learning environment were found to enhance the child’s ability to adapt and participate in class activities. These findings highlight the significance of implementing the ABA method and emphasize the teacher’s vital role as a facilitator in supporting the educational development of children with autism.